2012
DOI: 10.1038/ejcn.2011.205
|View full text |Cite
|
Sign up to set email alerts
|

Unrestricted consumption of fruits and vegetables in phenylketonuria: no major impact on metabolic control

Abstract: Background/Objectives: The treatment of phenylketonuria (PKU) requires consistent restriction of protein intake from natural sources. Therefore, protein from all foods has to be accounted for, even the small amounts in fruits and vegetables. We studied whether free consumption of fruits and vegetables containing less than 75 mg phenylalanine (phe) per 100 g affects metabolic control in children with PKU. Subjects/Methods: Fourteen children (2-10 years) were included in a cross-over study, with a two-week perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
2
42
0
1
Order By: Relevance
“…However, a special supplementation of vitamin C seems not to be necessary for PKU patients, as the most fruit and vegetables, the main sources for vitamin C, are low in protein and could be consumed in adequate amounts. Recent studies even showed that free consumption of fruits and vegetables does not impair the metabolic control in PKU patients (MacDonald et al 2003;Rohde et al 2012;Zimmermann et al 2012). Hence, independent from the therapeutic regimes (Phe restricted diet + AAM alone or in combination with BH 4 ) it should be the objective to encourage the patients to eat more fruits as well as vegetables, rather than supplementing vitamin C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a special supplementation of vitamin C seems not to be necessary for PKU patients, as the most fruit and vegetables, the main sources for vitamin C, are low in protein and could be consumed in adequate amounts. Recent studies even showed that free consumption of fruits and vegetables does not impair the metabolic control in PKU patients (MacDonald et al 2003;Rohde et al 2012;Zimmermann et al 2012). Hence, independent from the therapeutic regimes (Phe restricted diet + AAM alone or in combination with BH 4 ) it should be the objective to encourage the patients to eat more fruits as well as vegetables, rather than supplementing vitamin C.…”
Section: Discussionmentioning
confidence: 99%
“…In the classical treatment of PKU it is necessary to plan meals exactly and to calculate the Phe content of all foods. Only recently, some specialized centres allow the unrestricted consumption of fruits and vegetables under certain conditions (Macdonald et al 2003;Rohde et al 2012;Zimmermann et al 2012). However, the individual Phe tolerance has to be respected.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, although investigating small patient groups, could demonstrate the safety of dietary regimes without exact calculation of Phe from all ingested foods and beverages in children with classical PKU. These include investigations of small cohorts with respect to free use of fruits and vegetables in short-term [9], [11], as well as long-term settings [8], [10], [12]. The regimes 2, 3 and 4 revealed similar results, and in total represent a group of 80 patients.…”
Section: Discussionmentioning
confidence: 98%
“…Within this system, however, there are differences with respect to its degree of accuracy. So far, only few studies with small patient groups of children and adolescents were performed to examine the influence of dietary regimes on metabolic control [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation